Characterization of naturally occurring, new and persistent subclinical foot‐and‐mouth disease virus infection in vaccinated Asian buffalo in Islamabad Capital Territory, Pakistan. Issue 6 (23rd July 2018) - Farooq, Umer; Ahmed, Zaheer; Naeem, Khalid; Bertram, Miranda; Brito, Barbara; Stenfeldt, Carolina; Pauszek, Steven J.; LaRocco, Michael; Rodriguez, Luis; Arzt, Jonathan
Abstract: The convalescent subclinical carrier state of foot‐and‐mouth disease virus (FMDV) infection has been thoroughly investigated; contrastingly, the subclinical form of new infections of vaccinated and naïve hosts is recognized, but poorly understood. To investigate the natural dynamics of subclinical FMDV infections, a prospective, 12‐month, longitudinal study was conducted in vaccinated Asian buffalo ( Bubalus bubalis ) under natural conditions in Pakistan, where FMDV is hyperendemic. Oropharyngeal fluid (OPF) samples were obtained quarterly from 300 buffalo on 30 farms which reported no clinical FMD during the 12‐month study period. At the start of the study, 77.7% of buffalo had FMDV anti‐NSP antibodies, and all farms had at least one seropositive buffalo. Based upon the presence of viral RNA and viral VP1 sequences obtained, distinct subcategories of subclinical infections were documented, including new, persistent, and serial infections with different FMDV strains. Viral RNA was detected in at least one OPF sample from 180 (60%) of the 300 buffalo. Over the course of the study, FMDV was detected in OPF of 80 buffalo that had been FMDV‐free in previous OPF samples, indicating the occurrence of new subclinical infections. Eight buffalo were confirmed to be persistently infected, and serial infection with different FMDVs was confirmed in 13 animals. The most prevalent serotype detected was Asia‐1, followed by A, and O. Phylogenetic analysis indicated multiple distinct clusters of serotypes Asia‐1 and A. This study indicates a high prevalence of subclinical FMDV infection in vaccinated buffalo in Pakistan and emphasizes the importance of clinically undetected infection in FMD dynamics in endemic regions.